CORNEAL SENSITIVITY AS A QUANTITATIVE INDEX OF SENSORY NEUROPATHY IN PATIENTS WITH NIDDM - MORITA, Masako; TODO, Ryohei; TODO, Naomi; SHIMODA, Tomoko; KATSURA, Masaru (Japanese Journal of National Medical Services, 1995)
We investigated usefulness of corneal sensitivity as a quantitative index of sensory neuropathy in diabetic patients. Subjects were 167 patients with NIDDM. Their age ranged from 28 to 65 years old. Corneas exmined showed no erosive lesions which could affect corneal sensitivity. Corneal sensitivity was measured with a Cochet & Bonnet aesthesiometer with a nylon filament 0.12 mm in diameter. The length of the filament was decreased by 10 mm until a patient could perceive the exact number of the filament's attachments to the cornea. Estimation was carried out in 3 portions of the cornea and we perfomed this study by using the mean value for a total of 6 portions in both eyes. Statistical analysis was made to corroborate correlation between corneal sensitivity and other indices of diabetic complications including subjective symptoms of sensory neuropathy, coefficient of variation of R-R intervals in electrocardiograms, urinary excretion rate of microalbumin and retinal status. Corneal sensitivity was significantly correlated with these parameters, respectively. When comparison was made between patients with decreased corneal sensitivity and age-and sex-matched groups with normal corneal sensitivity, motor and sensory nerve conduction velocities were found to be significantly decreased in the former. These data suggest that measurement of corneal sensitivity offers a simple and quantitative test of sensory neuropathy in diabetic patients.